Hiperglicemia como risco para mortalidade de pacientes com septicemia em unidade de terapia intensiva - Moreira, Adriana Cristina (2017)
Overall objective: To evaluate the correlation and presence of hyperglycemia in patients with sepsis, both clinical and surgical, as a morbidity and mortality factor. Method: This is a retrospective cohort study by means of the electronic medical record analysis of patients admitted to the Intensive Care Unit (ICU) of a large school hospital in the municipality of. Main results: The present study included 263 patients. The mean age of the patients was mostly between 14-59 (137 - 52.09%), followed by 126 (47.91%) with 60 years or more. The majority of the patients were male (147 - 55.89%) and Caucasian (226 - 85.93). The number of ICU deaths was 37 (14.07). The majority of the patients were male (91%) of the patients had diabetes mellitus (147 - 55.89%), Caucasian (226 - 85.94%) and non - diabetic patients (216 - (82.13%)), 241 (91.63%) hyperglycemic patients and 22 The majority of patients in this study were elderly, non-elderly, white, non-elderly, non-elderly, non-elderly, non-elderly, And in the non-diabetic group, presented hyperglycemia in the first 24 hours of hospitalization at the Intensive Care Unit. In response to the objective of the study, it was verified that hyperglycemia is a risk factor for mortality among patients with Sepsis patients admitted to the Intensive Care Unit. The glycemic control in the ICU is an important strategy for Routine care of critically ill patients. There are evidences that reinforce the need to deepen the mechanism of action of this disease, which is currently one of the main causes of deaths in the ICU.